Convergence in Emerging Europe : Sustainability and Vulnerabilities - Vamvakidis, Athanasios (Washington, D.C. : International Monetary Fund, 2008)
The emerging European economies have been converging rapidly towards the more advanced European economies in recent years. However, large external imbalances in parts of the region have raised questions about sustainability and concerns about vulnerabilities. Empirical evidence in this paper suggest that the convergence trend of emerging Europe is based on strong fundamentals and is expected to continue, but at a slower pace. Moreover, the convergence path may be volatile as countries with large external imbalances adjust, with risks of a hard landing in some cases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet